Inflammation Is Present in De Quervain Disease—Correlation Study Between Biochemical and Histopathological Evaluation. (May 2015) - Kuo, Yao-Lung; Hsu, Che-Chia; Kuo, Li-Chieh; Wu, Po-Ting; Shao, Chung-Jung; Wu, Kuo-Chen; Wu, Tung-Tai; Jou, I-Ming
Abstract : Background: De Quervain disease is a stenosing condition of the sheath of the abductor pollicis longus and extensor pollicis brevis tendons at the radial styloid process. Previous studies consistently reported that the pathological change of this condition is thought to be primarily an extensor retinaculum thickened by fibrosis and angiogenesis instead of inflammation. Contradictorily, the conservative treatment for de Quervain disease is anti-inflammatory medication. The inflammatory response may be involved in this disease; however, there is no present study directly evidencing whether the inflammatory responses exist in de Quervain disease or not. The histopathology of de Quervain disease is yet to be elucidated clearly. Purpose: To grade all specimens in the different stages and characterize specific inflammatory cell and factors to examine whether inflammatory response is involved in de Quervain disease. Methods: Retinaculum samples were collected from 13 patients with de Quervain disease after surgery. The specimens were evaluated histologically by collagen structure grading and immunohistochemically by quantifying the presence of neutrophil elastase, macrophages, cyclooxygenase, and vascular endothelium. Results: Neutrophil elastase and cyclooxygenase occur in the de Quervain disease retinaculum and increased with the grade of collagen structure. After angiogenesis, macrophage infiltration occurs in the grade II matrix worse than grade III matrix. Conclusions: Inflammation is present in de Quervain disease. This study provides direct evidence for inflammatory cell and infiltration factors and offer valuable clues for specific pharmacological therapies for de Quervain disease.